Output Over Effort: Management Control System and Performance in Indonesian Higher Education Institutions - Darmawan, Rahmat; Amalia, Rizka; Al-Maghrebi, Mohammed Saleh (Public Accounting and Sustainability, 2025)
Research aims: This study examines the influence of management control systems, comprising input control, behavioral control, and output control, on the performance of higher education institutions (HEIs) in Indonesia. It also investigates the moderating role of work stress in these relationships. Design/Methodology/Approach: The research employed a quantitative survey method involving 581 HEIs selected through purposive sampling. Data were collected using a structured questionnaire and analysed through Partial Least Squares Structural Equation Modeling (PLS-SEM), multigroup analysis, and predictive assessment using PLSpredict. Research findings: The results show that output and behavioral control significantly affect performance, while input control does not. Although job stress was conceptually proposed as a moderator, it did not significantly moderate the relationship between management control systems and performance across different types of institutions, both public and private HEIs. Output control emerged as the most consistent and strong predictor of performance, particularly within public institutions. Theoretical contribution/Originality: This study contributes to the development of Goal Setting Theory and Job Demands Resources Theory by integrating work stress as a contextual factor in the relationship between control mechanisms and performance. The study offers a more comprehensive understanding of performance governance in academic settings. Practitioner/Policy Implication: The findings suggest that higher education leaders should strengthen output-based control systems and adopt proactive strategies to address work stress to sustain lecturer performance. Institutional policies should be context-sensitive and oriented toward both productivity and well-being. This study also supports sustainability in HEIs by aligning performance systems with long-term academic resilience and inclusive development goals.